2003
DOI: 10.1117/12.515663
|View full text |Cite
|
Sign up to set email alerts
|

<title>Large-scale first-principles calculations of Fe-doped SrTiO<formula><inf><roman>3</roman></inf></formula></title>

Abstract: The energy level positions in the optical gap and atomic geometry for the Fe4 impurity substituting for a host Ti atom in SrTiO3 are calculated using the Unrestricted Hartree-Fock (UHF) method and supercells containing up to 320 atoms. In agreement with experiment, the high spin (S=2) state is much lower in energy than the zero-spin state. The energy level positions strongly depend on the asymmetric displacements of six nearest 0 ions which is a combination of the Jahn-Teller and breathing modes. A considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…22, there is a scatter of around the Salpeter value. Piskunov (1976) analysed the MF slopes of 61 open star clusters and found an average value of in the mass range of 1 to 25 M ⊙ . Similarly, in five young and well‐populated open clusters, Sagar et al (1986) derive an average value of within the mass range of 1.3 to 80 M ⊙ .…”
Section: Luminosity and Mass Functions Of The Clusters Under Studymentioning
confidence: 99%
“…22, there is a scatter of around the Salpeter value. Piskunov (1976) analysed the MF slopes of 61 open star clusters and found an average value of in the mass range of 1 to 25 M ⊙ . Similarly, in five young and well‐populated open clusters, Sagar et al (1986) derive an average value of within the mass range of 1.3 to 80 M ⊙ .…”
Section: Luminosity and Mass Functions Of The Clusters Under Studymentioning
confidence: 99%
“…In recent years, luminosity and mass functions have been determined for a number of open clusters using homogeneous photoelectric or CCD data and reliable cluster membership criteria (cf. Piskunov 1976;Sagar et al 1986Sagar et al , 1988Scalo 1986Scalo , 1998Kjeldsen & Fransden 1991;Phelps & Janes 1993;Massey 1995;Durgapal & Pandey 2001;Pandey et al 2005Pandey et al , 2007 and references therein). Although the average slope of the MF does not seem to be very different from the Salpeter (1955) value, Pandey et al (2001Pandey et al ( , 2005 found that the nature of the MF in open clusters does not remain the same over the entire region of the cluster and the slope of the MF steepens as radial distance from the cluster center increases.…”
Section: Introductionmentioning
confidence: 99%